Environmental economics : theory and policy in equilibrium - Wiesmeth, H. (Hans) (Springer texts in business and economics., 2012)
This text covers essential areas of environmental theory and policy, including international environmental problems. The approach, based on rigorous theory, shows how economic principles can aid in understanding environmental issues and can guide policymakers.